An autoethnography of hunting - Presser, Lois (Crime, law and social change, 2011)
To better understand why we do harm by killing and eating nonhuman animals, we engaged in autoethnography. We used reflections on our harmful behavior to understand harmful behavior more generally. Our method first and foremost was to be as honest as we know how to be. The process of reflecting on our behavior had us moving through a series of questions that organize the essay. We also referred to scholarly literature on violence and on hunting to challenge our thoughts. In this way we arrived at insights on aspects of doing harm, including the role of positioning the target in a certain way; not thinking about the harm and the institutional supports for not thinking; the particular lure of power through killing; and the problematic indictment of hunting by meat-eaters.